The procedural criteria that condition the administrative Sanctioning power - Hernández-Mendible, Víctor Rafael (2020)
This study analyzes how the criteria developed by the Inter-American Court of Human Rights can serve as guidance to the national organs that exercise the Public Power, so that in exercising their powers they guarantee due administrative procedure, the right to defense and presumption of innocence, when exercising the administrative sanctioning power.